Barlow versus Hebb: When is it time to abandon the notion of feature detectors and adopt the cell assembly as the unit of cognition?. (27th July 2018) - Eichenbaum, Howard
Highlights: In higher order areas and complex tasks, neurons exhibit mixed selectivity and dependence on cognitive demands. These properties are observed in inferotemporal cortex, prefrontal cortex, and the hippocampus. New population analyses reveal how cell assemblies in these brain areas organize task relevant knowledge. Abstract: Research on how information is encoded by the brain is largely based on studies of feature detector properties of single neurons, but considerable new data shows that single neurons in many brain areas have mixed selectivity for multiple features and change their tuning properties across realistic information processing situations. Here I consider new approaches that explore cell assemblies as the units of information processing and how these approaches are revealing the structure and organization of neural representations in perception and cognition.